Norm contestation in the digital era: campaigning for refugee rights. (1st May 2019) - Hall, Nina
Abstract: Activists in the internet era are taking action through online petitions, twitter storms and by forming new digital advocacy organizations such as Campact, 38 Degrees and GetUp!. However, no International Relations (IR) scholarship has systematically examined the role of digital advocacy organizations in norm contestation. Digital advocacy organizations warrant study given their international reach, their large memberships, their longevity, their frequent campaigning activity and their claimed impact. This article focuses on the responses of three digital advocacy organizations in Australia, the UK and Ireland to the same external crisis: an increasing number of refugees worldwide. It asks: when and why did these organizations engage in behavioural norm contestation during the refugee crisis? Their use of behavioural contestation is a puzzle, given that digital advocacy organizations have low implementation power. The article draws on interviews with activists and experts, and finds that advocacy groups firstly use discursive contestation (debating the meaning and importance of norms), and then may engage in behavioural contestation (influencing the implementation of norms). Discursive contestation is less costly, and perceived to be less effective, than behavioural contestation. The article suggests that digital advocacy organizations can mobilize people online and offline, and IR scholars should examine this important source of power. This article forms part of the special section of the May 2019 issue of International Affairs on 'The dynamics of dissent', guest-edited by Anette Stimmer and Lea Wisken.